The Effect of Physical Environment on Student Learning Comfort at SMPN 4 Jember - Ainurrohmah, Silfia; Prihandono, Trapsilo; Yushardi, Yushardi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2024)
Good learning when a person yarg does learning is happy in the performance of learning. Fun and well-being in learning can come from student comfort, student comfort can come from extemporaneous environmental factors such as temperature, humidity, noise, lighting, infrastructure. Therefore the purpose of this study is to analyze the physical environment of the students' learning convenience in SMPN 4 Jember. A measured physical environment is temperature, humidity, noise, lighting, WiFi signals. The method used is descriptive. The result is students are uncomfortable, students are uncomfortable at temperature, noise, Wi-Fi signals and students feel quite comfortable on the humidity and lighting.